2020
DOI: 10.3389/fimmu.2020.02190
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel HIF-1α-αMβ2 Integrin-NET Axis in Fibrotic Interstitial Lung Disease

Abstract: Neutrophilic inflammation correlates with mortality in fibrotic interstitial lung disease (ILD) particularly in the most severe form, idiopathic pulmonary fibrosis (IPF), although the underlying mechanisms remain unclear. Neutrophil function is modulated by numerous factors, including integrin activation, inflammatory cytokines and hypoxia. Hypoxia has an important role in inflammation and may also contribute to pulmonary disease. We aimed to determine how neutrophil activation occurs in ILD and the relative i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 88 publications
(125 reference statements)
0
12
0
Order By: Relevance
“… 155 , 156 Furthermore, neutrophils and their products have been implicated in lung fibrogenesis in other chronic lung diseases such as interstitial lung disease (ILD). For example αMβ2 integrins can regulate neutrophil extracellular trap (NET) formation in ILD, 157 and secretory leukocyte protease inhibitor (SLPI), which inhibits neutrophil elastase, has differential effects on collagen expression in mouse lung tissue. 158 Previous work has shown that integrin expression by sputum neutrophils in asthmatic patients is aberrant compared with healthy controls, 159 however, whether such changes in integrin expression affect the overall activity of neutrophils in asthma and the impact this has on airway remodeling is yet to be elucidated.…”
Section: Integrins In Airway Remodeling: Inflammationmentioning
confidence: 99%
“… 155 , 156 Furthermore, neutrophils and their products have been implicated in lung fibrogenesis in other chronic lung diseases such as interstitial lung disease (ILD). For example αMβ2 integrins can regulate neutrophil extracellular trap (NET) formation in ILD, 157 and secretory leukocyte protease inhibitor (SLPI), which inhibits neutrophil elastase, has differential effects on collagen expression in mouse lung tissue. 158 Previous work has shown that integrin expression by sputum neutrophils in asthmatic patients is aberrant compared with healthy controls, 159 however, whether such changes in integrin expression affect the overall activity of neutrophils in asthma and the impact this has on airway remodeling is yet to be elucidated.…”
Section: Integrins In Airway Remodeling: Inflammationmentioning
confidence: 99%
“…to have functional roles in driving bleomycin-induced brosis in mice [45][46][47][48] Evidence of increased neutrophil activation and NET formation in lung tissue and BAL uid from brotic ILD patients has also been shown, possibly driven by hypoxia and upregulation of HIF-1α 49 . Furthermore, upregulation of genes related to pulmonary brosis, as well as those for neutrophil activation and NETosis have been demonstrated in acute fatal COVID-19 50 , further emphasising the central role of these processes in acute severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Khawaja et al demonstrated that the hypoxic condition and HIF-1α upregulation may augment neutrophil recruitment and activation within the lung interstitium. Of note, in both PF and COVID-19, a progressive loss of lung functionality is evidenced that can lead to hypoxia phenomena sustaining the vicious loop of neutrophil activation [48] .…”
Section: Molecular Mechanisms Of Fibrosis: What Is Known and What Is Unknownmentioning
confidence: 99%